APLIKASI METODE NUMERIK DALAM PERHITUNGAN LUAS DAN VOLUME BADAN KAPAL YANG BERADA DI BAWAH PERMUKAAN AIR LAUT. - Sasono, Eko Julianto (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2006)
This research studied about application of numeric metode to calculate area and volume of ship under water. The numeric methode used in this research are trapesium and simpson methode as comparesion. Correction value condition must be less than 0.5 %. As the results, simpson methode is better than trapezium with correction value for midship area and volume displacement less than 0.5 %.